2009
DOI: 10.1001/jama.2009.856
|View full text |Cite
|
Sign up to set email alerts
|

Early Use of Polymyxin B Hemoperfusion in Abdominal Septic Shock

Abstract: EVERE SEPSIS AND SEPTIC SHOCK AREcommon problems in the intensive care unit (ICU) and carry a high mortality. Endotoxin, one of the principal components on the outer membrane of gram-negative bacteria, is considered relevant to their pathogenesis. High levels of endotoxin activity are associated with worse clinical outcomes. 1 However, effectiveness of endotoxintargeted therapy is still controversial. 2,3 Polymyxin B, an antibiotic with high affinity for endotoxin, has been bound and immobilized to polystyre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
567
13
17

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 722 publications
(618 citation statements)
references
References 39 publications
21
567
13
17
Order By: Relevance
“…However, as several new RCTs274, 275, 481 to investigate the utility of blood apheresis in the treatment of sepsis in adult patients have been announced successively in Europe and the United States, assessing the significance of this intervention for pediatric patients is believed to be valuable.…”
Section: Cq19: Pediatric Considerationsmentioning
confidence: 99%
“…However, as several new RCTs274, 275, 481 to investigate the utility of blood apheresis in the treatment of sepsis in adult patients have been announced successively in Europe and the United States, assessing the significance of this intervention for pediatric patients is believed to be valuable.…”
Section: Cq19: Pediatric Considerationsmentioning
confidence: 99%
“…Though still under evaluation in Europe and the US, polymyxin B hemoadsorption (Toraymyxin; Toray Industries, Inc., Tokyo, Japan) is widely used in Japan as a blood purification therapy and is covered by the Japanese national health insurance [42]. The EUPHAS (Early Use of Polymyxin B Hemoperfusion in Abdominal Sepsis) study was a prospective, multicenter randomized controlled study that was performed in 10 Italian intensive care units [43]. Sixty-four patients with severe sepsis or septic shock were randomly assigned to one of two groups (either conventional therapy or conventional therapy along with two sessions of polymyxin B hemoadsorption) within the 6 hours following emergency surgery for intra-abdominal infection.…”
Section: Hemoadsorptionmentioning
confidence: 99%
“…All patients enrolled in the previously published EUPHAS study had completed the two planned sessions of PMX with higher mortality observed in the control group 22. The incidence of cartridge clotting in the ABDO‐MIX study (11.4%; 25/220 sessions) was higher than in previous reports, such as 5.8% (4/68 sessions) in the EUPHAS study7 and 1.0% (12/1152 sessions) in the EUPHAS 2 study 25. Clotting problems in the blood circuit during PMX were seldom raised in Japan.…”
Section: Clinical Evidence For the Use Of Pmx In The Treatment Of Sevmentioning
confidence: 57%
“…The findings of a meta‐analysis demonstrated the favorable effects of PMX in 2007 6. The results of a subsequent RCT in Europe, the EUPHAS study (Early Use of Polymyxin B Hemoperfusion in Abdominal Sepsis), which was conducted in Italy, were published in 2009, showing that PMX results in a significant reduction in sepsis‐associated mortality 7. A large RCT, the ABDO‐MIX trial (Effects of Hemoperfusion with a Polymyxin B Membrane in Peritonitis with Septic Shock) in France, failed to show a survival benefit and improvement in organ failure with PMX compared to the conventional treatment of peritonitis‐induced septic shock 8.…”
Section: History Of the Development Of Toraymyxinmentioning
confidence: 99%
See 1 more Smart Citation